Analysis Activity Entrepreneur Through Bazaars in Elementary Schools - Tri Linggo Wati; Rizka Marela Nasir; Nafi'atuz Zukhruffah; Febrianti Masrum Bidhiana; Abil A'la At-Thoriq (P3I UMSurabaya, 2024)
Entrepreneurship involves the ability to establish, manage, and grow a business through creativity and innovation. According to Zimmerer, entrepreneurship focuses on applying innovative solutions to solve problems and capitalize on opportunities. A critical factor in entrepreneurship is mindset, which shapes an individual’s approach to innovation and decision-making. This study aims to analyze efforts to develop and enhance creativity in students by encouraging them to innovate from existing ideas in entrepreneurial activities at the elementary school level. The research employs qualitative methods, including observation and literature review, to explore strategies for fostering entrepreneurial mindsets in young learners. Findings highlight the importance of integrating creative exercises into entrepreneurial activities to nurture students' innovative thinking and problem-solving abilities, providing a foundation for future success in entrepreneurship.